2020
DOI: 10.1177/0300060519889187
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CASC11 was downregulated in coronary artery disease and inhibits transforming growth factor-β1

Abstract: Objective: To investigate the involvement of long non-coding RNA (lncRNA) Cancer Susceptibility 11 (CASC11) in patients with coronary artery disease (CAD). Methods: This case-control study enrolled patients with CAD and age-and sex-matched healthy control subjects. The plasma levels of lncRNA CASC11 and transforming growth factor-beta 1 (TGF-b1) were measured. Diagnostic values of lncRNA CASC11 and TGF-b1 for CAD were determined using receiver operating characteristic curve analysis. Correlations between plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…A prior study has discovered the downregulation of lncRNA CASC11 in CAD 15 . Therefore, we detected the expression pattern of CASC11 in CMECs and found that the expression levels of CASC11 were decreased with the increase in ox‐LDL concentration ( p < 0.01, Figure 2A).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…A prior study has discovered the downregulation of lncRNA CASC11 in CAD 15 . Therefore, we detected the expression pattern of CASC11 in CMECs and found that the expression levels of CASC11 were decreased with the increase in ox‐LDL concentration ( p < 0.01, Figure 2A).…”
Section: Resultsmentioning
confidence: 73%
“…LncRNA cancer susceptibility 11 (CASC11) is a well‐documented oncogene signature in a variety of cancer types 14 . To our knowledge, CASC11 is shown to be downregulated in the plasma of CAD patients 15 . However, there is no functional study on the role of CASC11 in CAD.…”
Section: Introductionmentioning
confidence: 81%
“…Expression of CASC11 has also been decreased in patients with CAD parallel with overexpression of TGF-β1. Functional studies revealed the impact of this lncRNA in the suppression of TGF-β1 expression in endothelial cells ( 19 ).…”
Section: Lncrnas and Cadmentioning
confidence: 99%
“…Expression of CASC11 has also been decreased in patients with CAD parallel with overexpression of TGF-β1. Functional studies revealed the impact of this lncRNA in the suppression of TGF-β1 expression in endothelial cells ( 19 ). Expression of LEF1-AS1 has been elevated in plasma and tissue samples of CAD patients, whereas expression of its target miRNA, i.e., miR-544a, has been decreased.…”
Section: Lncrnas and Cadmentioning
confidence: 99%
See 1 more Smart Citation